Refractive Lens Exchange Surgery in Early-Onset High Myopia Patients With Partial Cataract - Zhang, Xi-Fang; Li, Xiao-Xia; Xin, Chen; Kline, Brad; Kang, Meng-Tian; Li, Meng; Qiao, Li-Ya; Wang, Ning-Li (Frontiers in Medicine, 2022)
Purpose By reporting clinical characteristics and retinal image quality before and after refractive lens replacement surgery in early-onset high myopia (eoHM) patients presenting with partial cataract, we emphasized the need for an objective way to grade the severity of partial cataracts. Methods This retrospective, consecutive case series included six Chinese patients (nine eyes). Analysis of previous medical records, visual acuity, optometry, retinal image quality, and axial length (AXL) before surgery and after surgery was performed. Results Five females and one male (nine eyes) with a mean (± SD) age of 11.6 ± 7.9 years (range: 4–25 years) were included in this study. The preoperative spherical power ranged from −7.5 to −42 D. The mean follow-up time was 36 months (range: 24–48 months). Phacoemulsification was followed by in-the-bag implantation of intraocular lens. For patients who were under 6 years old, posterior capsulotomy + anterior vitrectomy were performed simultaneously. All surgeries were uneventful and no postoperative complications occurred during the entire follow-up period. All patients’ uncorrected visual acuity improved by ≥2 lines postoperatively(Snellen acuity). LogMAR best-corrected visual acuity was improved at 24-month (P = 0.042) and endpoint (P = 0.046) follow-ups. Modulation transfer function cutoff frequency (MTFcutoff) and objective scatter index (OSI) was significantly improved at 12-month (P = 0.025, P = 0.038), 24-month (P = 0.005, P = 0.007) and endpoint (P = 0.005, P = 0.008) follow-ups. Postoperative AXL remained stable during 2–4 year follow-ups (P > 0.05). Conclusion Refractive lens replacement surgery is safe and effective for improving functional vision in eoHM patients presenting with partial cataract. Retinal image quality could provide a useful and objective way to facilitate partial cataract severity evaluation and surgery decision making.